2004
DOI: 10.1051/0004-6361:20035901
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the CORS method for Cepheids radii determination based on Strömgren photometry

Abstract: Abstract. In this paper we present a modified version of the CORS method based on a new calibration of the Surface Brightness function in the Strömgren photometric system. The method has been tested by means of synthetic light and radial velocity curves derived from nonlinear pulsation models. Detailed simulations have been performed to take into account the quality of real observed curves as well as possible shifts between photometric and radial velocity data. The method has been then applied to a sample of G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 39 publications
(55 reference statements)
1
25
0
Order By: Relevance
“…Given this overall uncertainty, we decided to use two different values of the p factor: 1.36 and 1.27. These two values were chosen because they include the range of values found in the literature and, in particular, the value 1.36 was selected to allow comparison with our previous works (Ripepi et al 1997; Ruoppo et al 2004).…”
Section: Derivation Of the Radius Of Cepheidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this overall uncertainty, we decided to use two different values of the p factor: 1.36 and 1.27. These two values were chosen because they include the range of values found in the literature and, in particular, the value 1.36 was selected to allow comparison with our previous works (Ripepi et al 1997; Ruoppo et al 2004).…”
Section: Derivation Of the Radius Of Cepheidsmentioning
confidence: 99%
“…In a previous paper (Ruoppo et al 2004), we adapted the CORS method to derive Cepheid radii observed in the Strömgren system. However, the model atmospheres adopted in the quoted investigation to estimate the surface brightness did not allow us to include Cepheids with periods longer than 12–13 d. The cut‐off in the long‐period range limited the accuracy of the period–radius relation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, we face the problem of the LMC distance by means of the CORS version of the Baade-Wesselink surface brightness technique (Caccin et al 1981;Ripepi et al 1997Ripepi et al , 2000Ruoppo et al 2004;Molinaro et al 2011), using recent photometric and spectroscopic data of a sample of Cepheids observed in the populous cluster NGC 1866. This object is one of the few young (∼10 8 yr; Brocato et al 1989) LMC clusters that are close enough to allow for detailed observation of individual stars (see, e.g., Mucciarelli et al 2011;Brocato et al 2003, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic RV curves for Cepheids have been calculated from new pulsation models by Petroni et al (2003) and Ruoppo et al (2004). Biazzo et al (2004) elaborated a method for measuring simultaneously the temperature and radial velocity of Cepheids from line-depth ratio.…”
Section: Classical Pulsators (Cepheids Rr Lyrae Type Variables)mentioning
confidence: 99%